Benthic Macroinvertebrates along the Haraz Downstream in Southern Caspian Sea Basin: In Gradient of the Physicochemical Parameters - Ghasemi, Amir Faraz; Kamali, Morteza (International Journal of Zoology, 2014)
The Haraz River is one of the most important rivers in the Caspian Sea basin. In order to investigate changes in the taxa abundance composition and feeding groups of the benthic macroinvertebrates, twelve-time sampling was carried out at nine stations along three different sites: (1) before, (2) into, and (3) after Amol City. Results showed impacts of anthropogenic activities caused by the urbanization and development on the occurrence of benthic macroinvertebrates taxa. Families, Hydropsychidae and Heptageniidae at site 1 and Tipulidae at sites 2 and 3, were significantly dominant. The feeding groups of gathering collectors and predators increased from site 1 to site 3, while the filtering collectors and scrapers decreased. Consequently, our data supported the use of the bioindicator concept for Haraz River. Some sensitive (Hydropsychidae, Heptageniidae, Baetidae, and Leuctridae) and tolerant families (Tipulidae and Naididae/Tubificidae) are introduced as potential bioindicators of clean and disturbed river’s area, respectively.